Bank instability: interbank linkages and the role of disclosure - König-Kersting, Christian; Trautmann, Stefan T.; Vlahu, Razvan (Bank of Finland research discussion papers, 2020)
We study the impact of disclosure about bank fundamentals on depositors' behavior in the presence (and absence) of economic linkages between financial institutions. Using a controlled laboratory environment, we identify under which conditions disclosure is conducive to bank stability. We find that bank deposits are sensitive to perceived bank performance. While banks with strong fundamentals benefit from more precise disclosure, an opposing effect is present for solvent banks with weaker fundamentals. Depositors take information about economic linkages into account and correctly identify when disclosure about one institution conveys meaningful information for others. Our findings highlight both the costs and benefits of bank transparency and suggest that disclosure is not always stability enhancing.
Keywords: Graue Literatur